PERAN KOMUNIKASI INTERPERSONAL BARTENDER DALAM MEMBENTUK KEPUTUSAN PEMBELIAN DAN KEPUASAN PELANGGAN PADA BAR DAN CAFÉ DI KABUPATEN PALI - Rahmania Ananda Putri; Enos Julvirta; Gilang Ramadhan; Wientor Rah Mada; Nikson Hendra Lumbantoruan; M. Algi Fachri Akbar (Jurnal Manajemen Perhotelan dan Pariwisata, 2026)
This study aims to examine the effect of bartender interpersonal communication on customers’ purchase decisions and the effect of purchase decisions on customer satisfaction at bars and cafés in PALI Regency. A quantitative approach with an explanatory research design was employed. Data were collected through questionnaires administered to 70 customers selected using a purposive sampling technique. Data analysis was conducted using descriptive statistics, validity and reliability tests, and simple linear regression. The results revealed that bartender interpersonal communication had a positive and significant effect on customers’ purchase decisions (β = 0.641; p < 0.001). Furthermore, purchase decisions had a positive and significant effect on customer satisfaction (β = 0.713; p < 0.001). The findings indicate that effective bartender interpersonal communication helps customers obtain relevant information and select products that best suit their preferences, thereby enhancing customer satisfaction. This study highlights the importance of interaction quality between bartenders and customers as an essential component of customer experience in the hospitality industry.